Economic Implications of Churches in the Development of Human Settlemets. Study Case: Iasi City - Alexandra Georgiana Parasca (CES Working Papers, 2014)
It is not wrong said that monasteries and churches were one of the elements that led to the development of human settlements in Iasi, especially the city of Iasi. Most churches/monasteries from the feudal period, received from princes / noblemen vast areas of land in order to develop economically, so buildings can survive in time, but also the administrators. Gradually, this lands got to be populated by those who worked and eventually they built houses to live closer to the land they worked on. Subsequently, these small settlements led to the formation of rural settlements and with time they gained an urban character. Today, we have reached the stage where these religious buildings have grown importance in the development of tourism, attracting tourists from around the country and abroad.
Keywords: N93; N94; 330; churches; human settlements; development; Iasi